Acoustic Surface Wave Generation over Rigid Cylinder Arrays on a Rigid Plane - Berry, David (2020)
Propagation of an airborne acoustic pulse from a point source above an array of regularly spaced rigid cylinders on a rigid plane has been investigated using a two-dimensional multiple scattering theory. Time domain simulations show a main arrival and a separate delayed “tail.” Fourier analysis of the tail shows that, for a sufficiently sparse array of cylinders, it is composed of a series of spectral peaks resulting from constructive interference consistent with Bragg diffraction theory and amplitudes depending on the spacing and size of the cylinders. For increasingly compact distributions of cylinders, the lowest frequency peak is dominated by a quarter wavelength “organ pipe” or “gap” resonance in the space between the cylinders. Simulated pressure maps show that there is a transition region in the acoustic field with an extent that depends on the spacing and size of the cylinders. Beyond this region, individual gap resonances combine to create a field that declines exponentially with height, consistent with the behaviour of a surface wave. Data from measurements of acoustic pulses above copper cylinders on rigid fibreboard under anechoic conditions demonstrate some of the predicted characteristics.